Productive Performance, Serum Antioxidant Status, Tissue Selenium Deposition, and Gut Health Analysis of Broiler Chickens Supplemented with Selenium and Probiotics—A Pilot Study - Shengting Deng; Shengjun Hu; Junjing Xue; Kaili Yang; Ruiwen Zhuo; Yuanyuan Xiao; Rejun Fang (Animals, 2022)
The effect and interaction of dietary selenium (Se) and probiotics on three yellow chicken growth performance, tissue Se content, antioxidant capacity, and gut health were studied from 0 to 70 days of age. A total of 400 one-day-old broilers were distributed into four groups (I-Se, O-Se, I-Se + pros, and O-Se + pros groups) consisting of a 2 × 2 factorial design. The main factors were the source of Se (I-Se = inorganic Se: 0.2 mg/kg sodium selenite; O-Se = organic Se: 0.2 mg/kg Selenium yeast) and the level of probiotics (0.5% EM or 0% EM, the component of EM mainly includes Lactobacillus and Yeast at the dose of 2 × 108 cfu/kg and 3 × 107 cfu/kg, respectively). Each treatment had 5 duplicates consisting of 20 broilers. The results showed that the I-Se group had a greater (p < 0.05) ratio of feed: weight gain (F/G) of broilers at Starter (0–35 d) than the other treatments. Compared to the I-Se group, the O-Se group increased (p < 0.05) Se concentrations in the liver, pancreas, breast muscles, thigh muscle, and the activity of total antioxidative capacity (T-AOC) in serum, as well as the relative abundance of Barnesiella and Lactobacillus in cecum. Meanwhile, probiotics enhanced (p < 0.05) Se concentrations in the pancreas, thigh muscle, serum, and the activity of T-AOC and glutathione peroxidase (GSH-Px), the duodenum’s ratio of villi height to crypt depth (V/C), the jejunum villus height and V/C, and the ileum’s villus height. Furthermore, the significant interactions (p < 0.05) between Se sources and the level of probiotics were observed in Se concentrations in the pancreas, thigh muscle, serum, crypt depth of duodenum, and villus height of jejunum of birds, and Barnesiella abundance in the cecal. In conclusion, our results demonstrate that the combination of O-Se + pros can improve broiler early growth performance, tissue Se content in the pancreas, thigh muscle, and serum, promote intestinal development, and regulate the composition of intestinal flora, suggesting a better combination. These findings provide an effective method of nutrient combination addition to improving the performance of three yellow chickens.